First direct observation of sputtered lunar oxygen. Issue 2 (14th February 2014) - Vorburger, A.; Wurz, P.; Barabash, S.; Wieser, M.; Futaana, Y.; Holmström, M.; Bhardwaj, A.; Asamura, K.
Abstract We present the first direct measurement of neutral oxygen in the lunar exosphere, detected by the Chandrayaan‐1 Energetic Neutral Analyzer (CENA). With the lunar surface consisting of about 60% of oxygen in number, the neutral oxygen detected in CENA's energy range (11 eV−3.3 keV) is attributed to have originated from the lunar surface, where it was released through solar wind ion sputtering. Fitting of CENA's mass spectra with calibration spectra from ground and in‐flight data resulted in the detection of a robust oxygen signal, with a flux of 0.2 to 0.4 times the flux of backscattered hydrogen, depending on the solar wind helium content and particle velocity. For the two solar wind types observed, we derive subsolar surface oxygen atom densities of N0= (1.1 ± 0.3) · 107m−3 and (1.4 ± 0.4) · 107m−3, respectively, which agree well with earlier model predictions and measured upper limits. From these surface densities, we derive column densities of NC= (1.5 ± 0.5) · 1013 m−2and (1.6 ± 0.5) · 1013 m−2. In addition, we identified for the first time a helium component. This helium is attributed to backscattering of solar wind helium (alpha particles) from the lunar surface as neutral energetic helium atoms, which has also been observed for the first time. This identification is supported by the characteristic energy of the measured helium atoms, which is roughly 4 times the energy of reflected solar wind hydrogen, and the correlation with solar wind helium content.